Regional Priority Analysis for Equal Distribution of Educational Facilities in West Java Using the Analytical Hierarchy Process (AHP) Method - Khusaeri, Ahmad (International Journal of Informatics, Economics, Management and Science, 2026)
Inequality in educational infrastructure remains a strategic challenge in West Java Province, where disparities in facility availability across regions hinder equitable access to education. This study aims to analyze and map regional priorities for the development of educational facilities (Elementary to Vocational High Schools) using the Analytical Hierarchy Process (AHP) method. Utilizing secondary data from 27 districts/cities, this study converts school availability data into standardized "Gap Scores." The criteria weighting results reveal that Vocational High Schools (SMK) have the highest urgency for intervention with a priority weight of 41%, followed by Senior High Schools (SMA) at 29%, Junior High Schools (SMP) at 21%, and Elementary Schools (SD) at 10%. This finding indicates a strong policy focus on vocational education. Based on the final synthesis, Kuningan Regency ranks first in development priority with a total score of 73.87%, followed by Majalengka Regency (69.84%) and Cirebon Regency (65.61%). Conversely, urban areas such as Bekasi City (6.92%) and Depok City (15.56%) show relatively adequate facility fulfillment. This study contributes a Data-Driven Decision Making model for the provincial government to allocate education infrastructure budgets more objectively, targeting regions with the highest disparities.